PENGARUH DOLOMIT TERHADAP SIFAT KIMIA TANAH, BAKTERI PELARUT FOSFAT, SERAPAN Ca, Mg, P DAN PRODUKSI JAGUNG MANIS - Nopriani, Lenny Sri; Ramadhani, Filka; Ishaq, Rizki Maulana; Kurniawan, Syahrul; Hidayat, Muhamad Taufiq; Albarki, Georona Kusma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
weet corn productivity in Indonesia is still in the low category. One of the causes is the problem of soil with low pH. Soil with a low pH causes the availability of nutrients to decrease, thereby inhibiting plant growth and development. Efforts can be made to add dolomite, because hydrolyzed dolomite can increase nutrient availability in the soil. Therefore, this research was carried out with the aim of analyzing the effect of adding various doses of dolomite on soil chemical properties, plant uptake of Ca, Mg and P, population of phosphate solubilizing bacteria, and sweet corn productivity in the Tegalan Land of Junrejo Village, Batu City, East Java. The research design used a randomized block design (RAK) consisting of 9 treatments with 3 replications. Treatment consisted of: M0 = control; M1 = 100% N, P, K; M2 = 100% N,P,K + 100% Kieserite; M3 = 100% N,P,K + 50% Dolomit; M4 = 100% N,P,K + 100% Dolomit; M5 = 100% N,P,K + 150% Dolomit; M6 = 75% N,P,K + 50% Dolomit; M7 = 75% N,P,K + 100% Dolomit; M8 = 75% N,P,K + 150% Dolomit. The data was analyzed for diversity using R studio software and continued with the DMRT (Duncan Multiple Range Test) test at 5% level. Next, to see the relationship and influence between parameters, correlation and regression tests were carried out. The findings demonstrated that adding 2.8 tonnes of dolomite per hectare might raise soil CEC (50.61%) and pH (13.41%). In addition, the addition of 4.2 tons/ha of dolomite was able to decrease soil P-available (5.65%), increase Ca-dd (26.4%), Mg-dd (85%), Ca absorption (165.12%), Mg absorption (366.67%), P absorption (78.57%), and sweet corn yield (78.04%). The addition of different doses of dolomite did not significantly alter the overall population parameter of phosphate-solubilizing bacteria. Furthermore, the link between sweet corn yield and nutritional absorption was both robust and weak. The increase in sweet corn output was impacted by P, Ca, and Mg absorption by 54.54%, 41.21%, and 42.79%, respectively.